Determinants Affecting the Use of the Internet by Older People - Blanka Klimova; Pavel Prazak; Petra Poulova; Ivana Simonova (Emerging Science Journal, 2021)
Objectives: The purpose of this study is to detect and analyze some factors which hinder or contribute to the positive use of the Internet by older people living in Central Europe, specifically in one region of the Czech Republic. Methods: The key method is a questionnaire whose results were processed by using a model of logistic regression. The research sample includes 432 seniors from senior houses, municipal ICT courses and the University of the Third Age, all coming from the region of Hradec Kralove in the Czech Republic. Findings: The findings of the proposed model confirmed that the key determinants in the Internet use by older people were age, previous experience with IT in their past occupation and active use of IT enhanced by some kind of training, in this case attending IT courses of the University of the Third Age. Education and gender have not proved to be significant determinants in this study. Novelty/ improvement: The introduced model of logistic regression enriches current literature on the subject by emphasizing the possible factors that influence the use of the Internet by seniors in the region. The survey also investigates which factors in comparison with each other act more and which less, and which factors are significant within the model and which are not. Doi: 10.28991/esj-2021-01317 Full Text: PDF